L’important, ce n’est pas que de participer ! - David Montembault; Élise Geisler (Projets de Paysage)
For the last twenty years, the number of participative approaches in the field of landscape architecture has increased. Although many different ideas have been experimented with, none of these has necessarily been firmly based on theoretical or methodological fundamentals. By making a detailed analysis of approximately twenty participative landscape projects carried out over the last fifteen years in Europe, we propose a "matrix" that can be used as a basis for reflecting on the implementation, analysis and/or evaluation of participative landscape projects. Our primary aim is to shed light on the conditions and means of implementation of these approaches adapted to targeted objectives.